Health Care Administration - Natiello, Thomas A. (Academy of Management Review, 1976)
This article presents reviews of several books including, “Principals of Hospital Administration,” by Jim McGibony, “The Care of Health in Communities: Access for Outcasts,” by Nancy Milio and “Introduction to Health Planning,” by D. C. Bergwall.